2023
DOI: 10.3390/antiox12030714
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester Suppresses Oxidative Stress and Regulates M1/M2 Microglia Polarization via Sirt6/Nrf2 Pathway to Mitigate Cognitive Impairment in Aged Mice following Anesthesia and Surgery

Abstract: Postoperative cognitive dysfunction (POCD) is a severe neurological complication after anesthesia and surgery. However, there is still a lack of effective clinical pharmacotherapy due to its unclear pathogenesis. Caffeic acid phenethyl ester (CAPE), which is obtained from honeybee propolis and medicinal plants, shows powerful antioxidant, anti-inflammatory, and immunomodulating properties. In this study, we aimed to evaluate whether CAPE mitigated cognitive impairment following anesthesia and surgery and its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Neuroinflammation with excessively activated microglia has been associated with the pathogenesis and progression of neurodegenerative diseases 46 . Increased experimental evidence has established that microglia-mediated inflammation is essential in postoperative cognitive dysfunction 47 , 48 . In this study, we demonstrated that sevoflurane induced the activation of the cGAS-STING pathway, which triggered NLRP3 inflammasome-associated neuroinflammation in microglia during POCD.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation with excessively activated microglia has been associated with the pathogenesis and progression of neurodegenerative diseases 46 . Increased experimental evidence has established that microglia-mediated inflammation is essential in postoperative cognitive dysfunction 47 , 48 . In this study, we demonstrated that sevoflurane induced the activation of the cGAS-STING pathway, which triggered NLRP3 inflammasome-associated neuroinflammation in microglia during POCD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in subarachnoid hemorrhage models, it was proven that the activation of the PPARγ/Nrf2 axis via netrin-1 reduced ferroptotic cell death through the enhancement of Gpx4 and coenzyme-Q10/ferroptosis suppressor protein-1 pathways (Chen et al 2023 ). Neuroprotective effects of the PPARγ/Nrf2/Gpx4 pathway against ferroptosis have also been described in an epilepsy model tested on rats (Wang et al 2023a , b , c ). Taken together, these results suggest that the PPARγ/Nrf2 axis might aid in targeting ferroptosis in several NDs.…”
Section: Nrf2 ↔ Endocannabinoid System Interactionsmentioning
confidence: 92%
“…For instance, Nrf2 raised the expression of the mitochondrial biogenesis-related protein PPARγ-coactivator 1α (PGC1α) in the hippocampus, prefrontal cortex, and amygdala (Khalifeh et al 2017 ). Several studies reported that Nrf2 activators enhance microglial polarization towards an M2 neuroprotective phenotype (He et al 2021a , b ; Tao et al 2021 ; Wang et al 2023a , b , c ). Nrf2 is also activated in astrocytes to counteract Fe 2+ -induced toxicity (Cui et al 2016 ).…”
Section: Nrf2 Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that CAPE inhibits amyloid β-peptide-induced neuro-inflammation and oxidative stress through modulation of the Nrf2/HO-1 pathway in Alzheimer’s disease patients [ 22 ]. Further, CAPE treatment promotes microglial M2 polarization and suppresses oxidative stress, producing a neuroprotective effect for postoperative cognitive dysfunction patients [ 23 ]. Although previous authors demonstrated CAPE to reduce inflammatory mediators after SCI [ 24 ], the regulatory effects and specific mechanisms of CAPE action on microglia-mediated neuro-inflammation and oxidative stress are unknown.…”
Section: Introductionmentioning
confidence: 99%